European standards for social protection of internally displaced persons - Бориченко, Катерина Валеріївна; Бориченко, К. В.; Бориченко, Екатерина Валерьевна; Borychenko, Kateryna V.; Коваль, Віктор Васильович; Коваль, В. В.; Коваль, Виктор Васильевич; Koval, Viktor V.; Гудзь, Анна Олександрівна; Гудзь, А. О; Гудзь, Анна Александровна; Hudz, Anna O.; et al. (Puig-Salabarría, S.C., 2019)
This article reveals the problem of social security of internally displeased persons. The scope of social protection directed at this category of population is not the same in different countries. Taking into account the origin of the authors of the article, the questions of social protection of internally displaced persons in Ukraine are described in detail. Special attention was paid to the need to provide people with the opportunity to exercise their rights and freedoms as well as the proper conditions for social rehabilitation, that has arisen before the state. As a result of the research – ways how to strengthen the social security, increase the level of social protection and make it more effective are proposed.

У цій статті розкривається проблема соціального забезпечення внутрішньо незадоволених осіб. Обсяг соціального захисту, спрямований на цю категорію населення, неоднаковий у різних країнах. Враховуючи походження авторів статті, детально викладено питання соціального захисту внутрішньо переміщених осіб в Україні. Особливу увагу було приділено необхідності надання людям можливості реалізовувати свої права і свободи, а також належних умов для соціальної реабілітації, що виникла перед державою. За результатами дослідження запропоновано шляхи посилення соціального захисту, підвищення його рівня та ефективності.
Borychenko K. European standards for social protection of internally displaced persons / K. Borуchenko, A. Hudz, V. Koval, I. Golubkova, A. Mazur // Revista Dilemas Contemporáneos: Educación, Política y Valores. – Vol. 7. - № 88 (SI). - Puig-Salabarría, S.C., 2019. - 30 p.
Keywords: social protection; social security; internally displaced persons; displacement; соціальний захист; соціальне забезпечення; внутрішньо переміщені особи; переміщення; Research Subject Categories::LAW/JURISPRUDENCE